2021
DOI: 10.1212/nxi.0000000000000990
|View full text |Cite
|
Sign up to set email alerts
|

Skin Reactions in Patients With Multiple Sclerosis Receiving Cladribine Treatment

Abstract: ObjectiveTo report 77 patients with multiple sclerosis (MS) who developed skin-related adverse events (AEs) following treatment with cladribine.MethodsWe evaluated our prospective bicentric cladribine cohort. Cladribine-treated patients with a skin AE were identified.ResultsTwo hundred thirty-nine cladribine-treated patients with MS were evaluated. Seventy-seven patients (32%) showed at least 1 skin AE at median 1 month after cladribine initiation (range: 1–12). Within first 3 months following last cladribine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 11 publications
2
14
0
2
Order By: Relevance
“…The most frequently reported AE was headache, which is in line with the findings from the clinical trial program (Cook et al, 2019;Giovannoni et al, 2010). A recent prospective bicentric cohort study reported skin reactions to be common after cladribine tablets (Rolfes et al, 2021). In our study, skin disorders including alopecia, acne, and dermatitis were reported in five patients (2.8%).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The most frequently reported AE was headache, which is in line with the findings from the clinical trial program (Cook et al, 2019;Giovannoni et al, 2010). A recent prospective bicentric cohort study reported skin reactions to be common after cladribine tablets (Rolfes et al, 2021). In our study, skin disorders including alopecia, acne, and dermatitis were reported in five patients (2.8%).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, patients initiating cladribine tablets for MS were characterized by a high female to male ratio in contrast to previous cohorts (Bose et al, 2021;Lizak et al, 2021;Pfeuffer et al, 2021;Rolfes et al, 2021). The reason for the relative paucity of male individuals especially among treatment naive patients in this cohort is unknown.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Skin-related AEs, including shingles, were seen in 6%, including three previously reported cases of SASR. 21 A recent report on 239 pwMS treated with CladT detailed further skin reactions, and an overall incidence of 32%, 32 such that we conclude Litak ® does not harbour a higher risk of skin pathologies than the licenced oral compound or indeed other highly effective immunotherapies used in MS. 33 Other AEs were rare. Of note, headaches were uncommon.…”
Section: Discussionmentioning
confidence: 52%
“…Skin reactions are listed in prescribing information as potential AEs during treatment with cladribine tablets [ 7 , 8 ]. Reports from clinical experience in two centers in Germany indicated that within 3 months following the last dose of cladribine tablets, hair thinning, skin rash, mucositis, and pruritus can be observed [ 100 ]. Case reports of three patients who developed severe rash 3–192 days after receiving subcutaneously administered cladribine have highlighted severe skin reactions as a rare, but important, potential AE during treatment.…”
Section: Management Of Patients Receiving Cladribine Tabletsmentioning
confidence: 99%